The influence of tacit and explicit knowledge sharing on organizational performance among manufacturing companies in Malaysia - Ang, Hong Loong; Noor Fzlinda Binti Fabeil; Pang, Y.Y (Human Resource Management Academic Research Society (HRMARS), 2022)
This study was conducted an exploratory study to investigate the extent to which tacit and explicit knowledge sharing affect organizational performance in Malaysia’s manufacturing companies. The findings revealed that the study support positive relationship between tacit and explicit knowledge sharing and organizational performance (i.e., financial, quality, and innovative performance) which consistent as claimed in the previous studies. Tacit and explicit knowledge sharing were examined upon their relationship with organizational performance because they have been clarified as one of the most extensively researched issues since the early development of organizational theory. However, this study’s result has found that tacit knowledge sharing did not have a significant relationship with innovative performance. For the methodology, this study applied quantitative approach through a self- administrated questionnaire and believed to be able to contribute to the importance of tacit and explicit knowledge as a fundamental source of knowledge sharing and a necessary precondition to boost a manufacturing company’s performance. 145 samples of the companies were collected and analyzed using Partial Least Squares structural equation modeling technique. Thus, this study can reflect its current performance and represent the true position of manufacturing companies in Malaysia.